The challenge of measuring multi-morbidity and its costs - Wittenberg, Raphael (Isr J Health Policy Res, 2015)
The ageing of the population across developed countries and beyond has increased the importance of examining multi-morbidity. The recent paper by Arbelle et al. [Isr J of Health Policy Res. 2014;3:29] on multiple chronic conditions in Israel’s Maccabi Health Care System (MHC) is a welcome and interesting contribution to the literature on this topic. They found that the prevalence of multiple chronic conditions among the MHC population rises with age, is lower for higher socioeconomic groups, and is higher than in a primary care population in Scotland studied by Barnett et al. [Lancet. 2012;380:37–43]. The difference in prevalence between the two studies is unlikely to reflect entirely, or probably even mainly, real differences in morbidity rates between the two countries. Systematic reviews have highlighted large differences in the prevalence of multi-morbidity in different studies. Although the Israeli and Scottish study used similar definitions and methods, the nature of the source data differed. It seems likely that the incentives to record the full range of patients’ conditions may differ between data sources depending on the uses of the data, which may in turn depend on the country’s health care financing system. If this is correct, it will complicate comparisons between different jurisdictions. It is important to consider not only the prevalence of multi-morbidity but also its costs to the health system and to wider society. Cost of illness studies can be helpful in informing decisions about prioritisation of resources. Multi-morbidity complicates such studies. The overall costs of health and social care for people with a specific condition would include costs relating to any comorbidities. To examine the marginal impact on overall costs of each condition among those with multiple conditions is likely to be complex and arguably not especially useful.